Antioxidant activity of ajwa date [phoenix dactylifera] seeds, stingless bee honey [trigona itama] and their combinations / Nurul Wahida Shuib - Shuib, Nurul Wahida (2020)
Oxidative stress, a physiological imbalance between antioxidant and oxidant in favor of oxidant is one of the major concern worldwide due to its pathological effect. Antioxidant equipped in human body serve as a shield to protect biological sites from emergence of free radicals in cells. This study focused on identifying potential antioxidant properties within Ajwa date (Phoenix dactylifera) seeds extract, stingless bee honey (Trigona itama) and their combination at three different ratios (1:1, 1:2 and 2:1) were tested through TPC, DPPH and FRAP assay. Percentage yield of date (Phoenix dactylifera) seeds extract obtained was 6.8% using 50% acetone as extraction solvent. Physicochemical test of stingless bee honey was done on three parameters to determine the purity of honey. T. itama honey contained 23.9% moisture, 0.7% ash and pH of 3.7. At 100 μg/ml of concentration, phenolic content of stingless bee honey and date seeds extract were 912.19 ± 3.54 μg GAE/g and 749.49 ± 3.73 μg GAE/g, respectively. Scavenging activity of stingless bee honey and date seeds extract at 100 μg/ml were 160.17 ± 0.11 μg AAE/g and 143.95 ± 0.07 μg AAE/g. At 100 μg/ml, FRAP value of stingless bee honey and date seeds extract were at 683.95 ± 3.62 μg AAE/g and 521.29 ± 5.42 μg AAE/g, respectively. As for combination test by DPPH assay, scavenging activity of date seeds extract : stingless bee honey (1:1), stingless bee honey : date seeds extract (1:2) and stingless bee honey : date seeds extract (2:1) were 209.32 ± 1.93 μg AAE/g, 224.83 ± 2.55 μg AAE/g and 217.33 ± 2.90 μg AAE/g, respectively. FRAP value of combination test were 716.48 ± 3.94 μg AAE/g for date seeds extract : stingless bee honey (1:1), 1486.05 ± 1.38 μg AAE/g for stingless bee honey : date seeds extract (1:2) and 876.11 ± 4.64 μg AAE/g for stingless bee honey : date seeds extract (2:1), respectively. The combination of samples of different ratios possessed high antioxidant activity compared to both samples alone. Through combination test, mixture of both samples have potential to be seen as a health-promoting product to fight the pathological effect of free radicals due to their antioxidant activity.